Development of a Road Protector Scores Models as an Indicator for Indonesian National Road Safety Performance Assessment from the Perspective of Drivers of Four or More Wheeled Motorized Vehicles - Muhammad Idris (International Journal of Social Service and Research, 2023)
This paper introduces the model of Star Rating Scores (SRS) or Road Protector Scores (RPS) for Indonesian National Roads from the perspective of motorized vehicle drivers with four or more wheels, which are explored from the characteristics of traffic accidents along Indonesia's national roads. This SRS model takes into account 2 different main parameters and 4 main parameters that are the same as the main parameters of the SRS International Road Assessment Program (iRAP) and a total of 51 road attributes. The two main parameters that differ from the SRS iRAP model are the parameters for rear-end collision andhead-to-side collision when turning around. While the 4 parameters are the same as head-to-side collision accidents at property access, single accidents run off the road head-on collision accidents, and accidents at intersections. At the initial stages, the National Road SRS model was designed using 51 road attributes. After analyzing using the Importance and Performance Analysis (IPA) method, 43 road attributes were successfully formulated for the SRS National Road model, consisting of 30 likelihood factor attributes, 10 severity factor attributes, 2 external traffic influence factor attributes, and 1 factor attribute operational speed. In addition, it is proven that the SRS National Road model is significantly different from the SRS iRAP model. The three main parameters of the National Road SRS model, namely the rear-end collision parameter, the head-to-side collision parameter when turning direction (U-turn), and the head to side parameter at property access are significantly different from the parameters of the SRS iRAP model.